Implementasi Teologi Manajemen Pada Pembangunan Dan Pengembangan Gereja Berbasis Eklesiologi Ramah Lingkungan - Manuahe, Yani Mick. R (PARADOSI: Jurnal Teologi Praktika, 2024)
This article explores the application of management theology in the building and development of churches based on eco-friendly ecclesiology. The Church has a strategic role as a community of faith in facing the challenges of the global environmental crisis. By combining theological principles, resource management, and ecological responsibility, the church can be a driving force for change toward environmental sustainability. This approach includes environmentally friendly church building design, the use of energy-saving technology, waste management, and the integration of environmental education programs for congregations. This research uses qualitative methods through literature review and observation of church practices. The results show that the implementation of management theology is not only spiritually relevant, but also makes a real contribution to the preservation of ecosystems, making the church a role model for communities that support the sustainability of nature. Thus, the church is expected to be able to combine the values of faith and concrete actions in maintaining the integrity of God's creation